Gender differences in the association between childhood sexual abuse and risky sexual behaviours: A systematic review and meta-analysis. (January 2017) - Abajobir, Amanuel Alemu; Kisely, Steve; Maravilla, Joemer Calderon; Williams, Gail; Najman, Jake Moses
Abstract: This meta-analytic review examines the association between childhood sexual abuse and risky sexual behaviours with sub-group analyses by gender. Systematic searches of electronic databases including MEDLINE, PubMed, EMBASE, and PsycINFO were performed using key terms. We used a priori criteria to include high quality studies and control for heterogeneities across eligible studies. The review was registered with PROSPERO and used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The final meta-analysis applied fixed-effects model to generate pooled odds ratio (OR). Subgroup analyses were conducted to identify potential methodological moderators. The meta-analysis included 8 eligible studies ( N  = 38, 989, females = 53.1%). The overall syndemic of risky sexual behaviors at adulthood was 1.59 times more common in childhood sexual abuse victims. There was a similar association between childhood sexual abuse in general and subsequent risky sexual behaviors in both females and males. However, in cases of substantiated childhood sexual abuse, there was a greater odds of risky sexual behaviors in females (OR = 2.72) than males (OR = 1.69). The magnitude of association of childhood sexual abuse and risky sexual behaviors was similar for males and females regardless of study time, study quality score and method of childhood sexual abuse measurement. There were nonsignificant overall and subgroup differences between males and females. Childhood sexual abuse is a significant risk factor for a syndemic of risky sexual behaviors and the magnitude is similar both in females and males. More research is needed to explore possible mechanisms of association.